A legitimidade em questão e a questão da legitimação : análise do discurso do Grupo Gerdau em relação à Operação Zelotes - Galgano, Aurélia Decot (2019)
Corruption is a widespread phenomenon in many societies, which occupies great space in general public discourse and opinion of Brazil. It is commonly associated to the public sector, rather than the private one, even though it is common to have private organizations involvement in such cases. In sight of this privileged position of private organizations, we researched how one of them addresses discursively a case of corruption. The analyzed organization was Grupo Gerdau, a family business of the steel industry, at the occasion of its involvement with Operação Zelotes. The research was anchored on the concepts of social institutions and legitimation, to approach the themes of the relations between State and market, Brazilian ideology, the functioning of the market and corruption, with the intent of understanding the symbolic elements that touch corruption and private organizations. A qualitative and documental study was conducted, with data from Grupo Gerdau‟s institutional website, big media articles, the Comdinheiro database and Youtube. Discourse Analysis (AD) was used as method, with the notions of ethos and scenography, in order to identify how Grupo Gerdau defined itself, and how it inserted itself in national conjuncture at the time of Operação Zelotes. We found that Grupo Gerdau leans on and reinforces the opposition between State and maket, putting corruption on the side of inefficient State, and presenting itself as part of the efficient market. This discursive mechanism allows the distancing between Grupo Gerdau and Operação Zelotes, legitimizing the first one. We identified that there is a discursive system of ideological reinforcement, in which organizations present themselves as competent, leaning discursively on hegemonic ideology, at the same time that the market accepts such affirmation, grants social legitimacy to them and reinforces the current ideology. The work was delimited by the analysis of only one organization, and by the lack of statistic confirmation of the repercussion that Operação Zelotes had on market value of Grupo Gerdau. For future studies, we suggest an event study that accomplishes that confirmation, as well as the discourse analysis of more organizations.